Ethics and Institutions of Scientific Policy Advice - Überblick (Wirtschaftsdienst)
Abstract German policy advice is embedded in an institutional framework consisting of universities, research institutes, experts and advisory boards. Criticism of the German advisory landscape can be heard from time to time, for example that economic policy advice in Germany is not sufficiently oriented towards the latest research or that particular interests (e.g. of employers or employees) are heard too much. In addition, progress in empirical economics has strengthened the demand for “evidence-based policy advice”. What incentives do scientists have to participate in the policy discourse and what scientific ethos should they follow? The practical question arises as to how policy advice in Germany can be changed in order to enable the various voices from the scientific community as a whole to be heard more and to promote an open dialogue between researchers and policy-makers. What reforms in the science system and in the bodies advising policy would make sense in order to advise policy?